Updating Greenhouse Gas Inventory for the Livestock Sector in Southeast Sulawesi During the Year 2019-2020 - Siwi, La Ode; Yasin, Asramid (Universitas Halu Oleo, 2023)
The livestock sector GHG inventory aims to provide periodic information on the level, status, and trend of emission changes in Southeast Sulawesi as well as information on the achievement of GHG emission reductions in the livestock sector from climate change mitigation activities to determine Southeast Sulawesi mitigation and adaptation actions to GHG emissions. This inventory was carried out in Southeast Sulawesi in 2021. The data obtained were calculated using the Intergovernmental Panel on Climate Change (IPCC) model. The inventory results show the total emissions were 290.56 CO2eq Gg/year in 2019 and 313.86 CO2eq Gg/year. Keywords: GHG emissions, inventory, GHG mitigation